Hip-joint congruity after Dega osteotomy in patients with cerebral palsy: long-term results - Braatz, Frank; Klotz, Matthias C. M.; Wolf, Sebastian Immanuel; Dreher, Thomas (International orthopaedics, 2016)
IntroductionNeurogenic hip dislocation is quite common in children with cerebral palsy (CP). The purpose of this study was to evaluate the long-term outcome of single-event multilevel surgery (SEMLS) in combination with hip reconstruction by using a periacetabular osteotomy as described by Dega concerning post-operative remodeling and plasticity of the femoral head post-operatively.MethodsA total of 72 patients with CP as the primary disease and in whom a complex surgical hip reconstruction was performed during SEMLS between 1998 and 2004 were included in the study. There were 45 men and 27 women, with a median age of 7.6 (4.7-16.3) years at the time SEMLS was performed. The mean follow-up time was 7.7 years (4.9-11.8). X-rays were taken before and after surgery, and Rippstein 1 and 2 were used for follow-up. As the most reliable value for decentration, migration percentage (MP) as described by Reimers was used. To measure hip-joint cover at follow-up, the centre-edge angle was used. The hip was divided into four different categories according to sphericity and congruity. Using this approach, we could evaluate joint remodeling.ResultsPre-operatively, the mean MP measured by X-ray was 68 %. Directly after surgery, this value decreased on average by 12 % and at the long-term follow-up was 16.0 % on average. A high rate of incongruence was observed on X-rays taken directly after surgery: 66 hip joints were classified as incongruent. The number of aspherical and incongruent joints decreased to 54 at the follow-up examination.ConclusionData of our study with high plasticity of the hip joint suggest that even if the femoral head is deformed and a persistent incongruency after surgery is expected, hip reconstruction can be recommended.
Published online: 10 October 2015
Gesehen am 03.12.2018